Turned stem tension band technique in reverse total shoulder arthroplasty for proximal humeral fracture can achieve high tuberosity healing rates regardless of the vertical sutures - Kazumasa Takayama, MD; Hiromu Ito, MD, PhD (JSES International)
Background: The importance of tuberosity healing in reverse total shoulder arthroplasty for proximal humeral fractures (PHFs) has been recognized. The turned stem tension band (TSTB) technique has been applied to tuberosity repair, and high bone healing and low reduction loss rates have been reported. Vertical sutures were added to the original method to reinforce fixation. We hypothesized that vertical sutures would be unnecessary in case the supraspinatus tendon was resected. This study aimed to compare the TSTB technique with or without vertical suturing for PHFs and evaluate the rates of tuberosity healing and reduction loss. Methods: Thirty five patients (vertical suture group: 18 cases and nonvertical suture group: 17 cases) underwent reverse total shoulder arthroplasty for complex PHFs using the TSTB technique. We evaluated the postoperative range of motion, the American Shoulder and Elbow Surgeons score, tuberosity healing rates, and reduction loss. Results: The vertical and nonvertical suture groups showed no significant difference in flexion (119 ± 33° vs. 124 ± 23°, P = .95), abduction (116 ± 35° vs. 115 ± 27°, P = .78), external rotation (27 ± 12° vs. 21 ± 8°, P = .16), internal rotation (6 ± 4° lumbar 3 level vs. 6 ± 4°, lumbar 3 level P = .87), the American Shoulder and Elbow Surgeons (77.3 ± 10.7 vs. 81.6 ± 6.3, P = .59), Numerical Rating Scale scores (1.2 ± 0.9 vs. 0.8 ± 0.9, P = .13), and tuberosity reduction loss (P = .34). The tuberosity healing rate in both groups was 100%. Conclusion: The TSTB technique for PHFs provided high tuberosity healing and low reduction loss rates regardless of vertical sutures.